Evaluation of the Resistance of a Polypropylene Geotextile Against Ultraviolet Radiation. (19th June 2018) - Carneiro, José Ricardo; Almeida, Paulo Joaquim; Lopes, Maria de Lurdes
Abstract: The exposure to solar radiation (mainly due to the action of ultraviolet radiation) is one of the main causes for the premature failure of many polymeric materials, including the geotextiles. In this work, a nonwoven polypropylene geotextile (stabilized with a known amount of a hindered amine light stabilizer) was exposed to ultraviolet-aging tests, both in the laboratory (accelerated conditions) and outdoors (natural conditions). The damage occurred in the geotextile (caused by the ultraviolet-aging tests) was evaluated quantitatively (by monitoring changes in its mass per unit area, thickness, and tensile properties) and qualitatively (by scanning electron microscopy). The results, among other findings, showed that: (1) the ultraviolet-aging tests (both in the laboratory and outdoors) induced relevant damage in the polypropylene fibers of the geotextile (transverse cracks), leading to the deterioration of its tensile behavior, (2) the amount of degradation increased with the increase of the ultraviolet radiant energy, (3) the laboratory tests caused a faster deterioration of the polypropylene fibers than the outdoor tests, and (4) the degradation found by scanning electron microscopy in the polypropylene fibers correlated well with the deterioration occurred in the tensile behavior of the geotextile.